Mixed Matrix Membrane Chromatography Based on Hydrophobic Interaction for Whey Protein Fractionation - Syed Mohd Saufi, Tuan Chik; Fee, Conan J. (Elsevier Ltd, 2013)
The mixed matrix membrane (MMM) concept is extended, for the first time, to produce a hydrophobic interaction chromatography (HIC) membrane using crushed Phenyl Sepharose™ (GE Healthcare Technologies, Uppsala, Sweden) resin and tested for use in whey protein fractionation. The HIC MMM had static binding capacities (membrane volume basis) of 18.419±0.605 mg mL−1 for β-lactoglobulin, 45.850±2.753 mg mL−1 for α-lactalbumin, 41.106±9.004 mg mL−1 for bovine serum albumin and 42.467±4.130 mg mL−1 for lactoferin in individual protein solutions. For flowthrough whey fractionation, the adsorption performance of the HIC MMM was similar to a HiTrap™ Phenyl (GE Healthcare Technologies) HIC column. However, the well-known high processing speeds and inherently low pressure drops of MMM chromatography may offer benefits over a conventional packed bed column.